Features and Functions of Journals: A Preliminary Study - Bambang Yudi Cahyono (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract: This study is intended to describe the features and functions of journals written by EFL learners. The features described include the contents and organization of the journals. The functions examined in this study include sense of purpose and sense of audience in writing. The subjects of the study were students of the first semester who took English intensive course at the English Department of IKIP MALANG. The results of content analysis indicate that journals that the students write contain various themes. Analysis on paragraph organization indicates that paragraphs in the journals generally show adequate development. This study also shows that the student journals reflect sense of purpose and sense of audience in writing.